2019
DOI: 10.37358/mp.19.3.5223
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Dental Composite Resins and Saliva A comparative biochemical in vitro study

Abstract: This in vitro study analyses the biochemical interaction between saliva and three types of dental composite resins (a direct resin, an indirect resin and a dual-cure resin used for cementation of indirect dental restorations). The resin samples were obtained following a specific protocol and in line with the producers� recommendations; the resin samples were incubated with saliva samples collected from 19 healthy volunteers. The obtained results showed that the tested composite resins did not produce significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The obtained results of this study (that pointed out that the tested resins do not interfere with salivary oxidative stress), together with other reported data concerning composite resins’ biocompatibility, have clinical applicability, and highlight, increasingly, the special biological properties of these modern dental materials [ 2 ].…”
Section: New Elements From the Chemical Landscape Of Novel Composite Resinssupporting
confidence: 65%
See 3 more Smart Citations
“…The obtained results of this study (that pointed out that the tested resins do not interfere with salivary oxidative stress), together with other reported data concerning composite resins’ biocompatibility, have clinical applicability, and highlight, increasingly, the special biological properties of these modern dental materials [ 2 ].…”
Section: New Elements From the Chemical Landscape Of Novel Composite Resinssupporting
confidence: 65%
“…The in vitro study of Pantea et al revealed that the tested composite resins did not induce significant changes of the salivary redox status markers (uric acid, gamma glutamyl transferase, and oxidative stress responsive kinase-1) [ 2 ]. The tested dental composite resins were: a resin for direct dental restorations—GC G-ænial Posterior/GC Corporation/Tokyo/Japan—that have an organic matrix (UDMA/Urethane dimethacrylate/dimethacrylate co-monomer), filler, pigments and photo-initiators; a resin for indirect dental restorations—Gradia Lab Indirect Restoration System/GCCorporation/Tokyo/Japan—a nano-hybrid composite, having ultra-fine fillers with very high density and homogeneous distribution, mixed in the resin matrix; a composite resin for cementation of indirect dental restorations—G-Cem Link Force//GCCorporation/Tokyo/Japan—an universal dual cure resin cement.…”
Section: New Elements From the Chemical Landscape Of Novel Composite Resinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain aspects concerning the conventional and modern materials used for manufacturing interim prosthetic restorations represent important topics in present-day scientific research: the dimensional accuracy and mechanical behavior (compression strength, flexural strength, tensile strength, and wear resistance) [ 4 , 5 , 6 , 7 , 8 , 9 ]; color stability and reparability [ 10 , 11 , 12 ]; and chemical composition and biocompatibility issues (such as cytotoxicity, the materials’ interactions with oral epithelial cells, fibroblasts or dental pulp cells monomer release bacterial adhesion, biofilm formation, antimicrobial activity, and the materials’ interactions with saliva) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. With regard to biocompatibility, the results of various tests performed on saliva samples can contribute to establishing a diagnosis in diverse local or systemic diseases and to monitoring physiological or pathological conditions.…”
Section: Introductionmentioning
confidence: 99%